PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BIRO AKADEMIK DAN KEMAHASISWAAN UNIVERSITAS MULAWARMAN - La Saemi (Jurnal Paradigma (JP), 2019)
This study aimed to examine the employee development and discipline significant effect on the performance of employees At the Bureau of Academic and Student Affairs Mulawarman either partially or simultaneously and among these variables which has the dominant influence on employee performance At the Bureau of Academic and Student Affairs Mulawarman University. Type of this research is quantitative research. Collecting data in this study using a questionnaire or questionnaires. While the analytical tool used is multiple linear regression. The results showed the coefficient of determination (R2) of 0.478. This means that the variable of human resource development and labor discipline can explain changes in employee performance variable (Y) amounted to 47.8%, while the remaining 52.2% explained by other variables were included in this study model.Keywords: discipline, performance, development